PENGARUH TEKNIK ASSERTIVE TRAINING UNTUK MENINGKATKAN SELF ESTEEM SISWA MELALUI BIMBINGAN KELOMPOK DI SMK LABOR BINAAN FKIP UNRI - Andini, Dwi Indah; Rosmawati, Rosmawati; Mardes, Siska (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Self Esteem is an overall evaluation of self, which includes positive and negative judgments. Self Esteem also means how much we like ourselves. But there is a low self esteem that makes students feel inferior about being involved, not confident, blaming themselves caused by being criticized harshly, being ignored, even forcing something to perfect. One way to improve low self esteem is through assertive training techniques through group guidance. The purpose of this study is to describe the self esteem of students, to know the differences in the level of student self esteem, and the effect of the implementation of assertive training techniques in increasing student self esteem in group guidance. This type of research is a quantitative study using experimental methods using one group pretest-posttest design. The measuring instrument used in this study is the scale of self-esteem measurement consisting of 50 items before validation, and after the validity obtained valid items as many as 31 items with a validity of 0.300 and reliability of 0.893. The subjects of this study were 7 students from the Guided Labor Vocational School of the FKIP UNRI Pekanbaru who identified low self esteem. The data analysis technique used is the non-parametric statistical technique using the Wilcoxon test. The results of this study proved the hypothesis was accepted. It can be concluded that there are differences in self esteem of students before and after being given treatment in the form of assertive training techniques through group guidance. From the Spearman rank test obtained 0.847 while the r ^ 2 correlation coefficient is 0.16 thus the effect of assertive training techniques in increasing self esteem is 71%.Key Words: Assertive Training, Self Esteem